Exploring the Ecological and Medical Benefits of Dill (Anethum graveolens) as an Alternative to Spirulina (Arthrospira platensis) - Ulviyya, Mammadova (Dunakavics, 2024)
This study explores the potential of dill (Anethum graveolens) as a sustainable alternative to spirulina (Arthrospira platensis) in nutrition and health applications, specifically within Azerbaijani culture and broader ecological contexts. Dill, widely used in Azerbaijani cuisine and traditional medicine, offers significant ecological and medicinal benefits. Its culinary uses include flavoring various dishes, while its medicinal applications range from aiding digestion to enhancing immune function. Dill also plays an economic role in rural Azerbaijani communities, providing income through agriculture and appearing in cosmetics and personal care products. The study employs a comparative approach to examine the ecological sustainability, medicinal properties, and resource use of dill and spirulina. Laboratory analyses focus on antioxidant, antimicrobial, and anti-inflammatory properties, as well as the effects on human cells. The findings suggest that dill's ecological footprint and health benefits could make it a viable substitute for spirulina, especially in regions with suitable growing conditions. Furthermore, its cultural significance and economic value in Azerbaijan highlight dill's multifunctionality as a food, medicinal, and cultural product.